Microbial contribution to early marine cementation. Issue 2 (29th August 2021) - Diaz, Mara R.; Eberli, Gregor P.
Abstract: The origin of early marine cements is still being debated as either abiotic, triggered by evaporation and CO2 degassing, or microbially‐mediated. In particular, micritic envelopes and micritic meniscus cements have been proposed to be microbially‐mediated but the microbial community and the resulting organomineralization processes have rarely been documented. Herein, scanning electron microscopy and thin section analyses of samples from the Bahamas and Hamelin Pool, Australia, provide evidence that early cements in intergranular areas are the result of organomineralization processes driven by both active (microbial metabolism) and passive mechanisms influenced by mucilaginous extracellular polymeric substances and/or microbial cell walls acting as matrices for crystal nucleation and growth. Signatures of biogenicity are supported by the conspicuous presence of early micritic cements in association with dense filamentous fabrics and entombed microbial forms. Most importantly, the prolific colonization of metabolically active communities, many of which assist in carbonate precipitation, trapping, binding and encrustation of the grains, testifies to the contribution of microbes in early cementation processes. The extent and ubiquity of mucilaginous extracellular polymeric substances and its concomitant association with amorphous calcium carbonate nanograins indicates that passive organomineralization via an intermediary amorphous phase is the other leading process for the generation of micrite and fine mesh of aragonite needle‐like crystals. Furthermore, the conspicuous occurrence of microbially‐mediated micrite, meniscus and bridging cements, as well as microcrystalline Mg‐calcite cement in the marine phreatic realm challenges the widespread notion that these fabrics are indicative of marine vadose or quiet marine phreatic environments. All analyzed samples show a remarkable similarity in early cement fabrics and a consistent superposition of prismatic cements on the micrite meniscus and bridging cements. These microbially‐mediated micritic cements represent the first generation of marine cements upon which aragonite and high‐Mg calcite develop.